The Effect Total Physical Response Method on Students’ Vocabulary Mastery at SDN 182 Bengkulu Utara - Islakhiya, Maula; Susanto, Ferri; Anita, Anita (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to determine the effect of the Total Physical Response (TPR) method on improving the vocabulary mastery of fifth-grade students at SDN 182 Bengkulu Utara. Vocabulary mastery plays an essential role in English language learning, yet many young learners still face difficulties in understanding and retaining new vocabulary. This study employed a quantitative approach using a quasi-experimental design consisting of an experimental group taught with the TPR method and a control group taught with conventional learning methods. The sample consisted of 43 students selected through total sampling. The research instrument was a vocabulary test administered during the pre-test and post-test sessions. The findings revealed a significant improvement in the experimental group, with the average score increasing from 54.66 to 81.47, while the control group showed a smaller increase from 34.77 to 47.22. Statistical analysis indicated that the TPR method had a significant effect on students’ vocabulary mastery. Therefore, the Total Physical Response method is considered effective and suitable as an alternative method for teaching vocabulary to elementary school students.